Recessive omodysplasia: five new cases and review of the literature. - Elçioglu, N; Gustavson, K; Wilkie, A; Yüksel-Apak, M; Spranger, J (2004)
BACKGROUND: Autosomal recessive omodysplasia (MIM 258315) is a rare skeletal dysplasia characterized by severe congenital micromelia with shortening and distal tapering of the humeri and femora to give a club-like appearance. Fewer than 20 cases have been reported in the literature so far. OBJECTIVE: The purpose of this study was to more clearly describe the clinical and radiographic phenotypes and their changes with age. MATERIALS AND METHODS: Five new patients, including two sibs, with autosomal recessive omodysplasia are presented. RESULTS: Clinical features are rhizomelic dwarfism with limited extension of elbows and knees and a distinct face with a short nose, depressed nasal bridge, long philtrum, midline haemangiomas in infants and cryptorchidism in males. Radiological findings are distal hypoplasia of the short humerus and femur with characteristic radial dislocation and radioulnar diastasis. CONCLUSIONS: Based on a review of these and 16 previously reported patients, the regressive nature of the humerofemoral changes and the obvious male predominance are stressed. Phenotypic similarities with the atelosteogenesis group of disorders and with diastrophic dysplasia suggest common pathogenetic mechanisms.